2022
DOI: 10.1021/acs.jafc.2c04862
|View full text |Cite
|
Sign up to set email alerts
|

Rice Protein Peptides Alleviate Dextran Sulfate Sodium-Induced Colitis via the Keap1–Nrf2 Signaling Pathway and Regulating Gut Microbiota

Abstract: Inflammatory bowel disease (IBD), with increasing incidence, causes a range of gastrointestinal symptoms and brings distress and impact on the health and lives of patients. The aim of this study was to explore the protective effects of industrially produced rice protein peptides (RPP) on dextran sulfate sodium (DSS)-induced acute colitis in mice and the potential mechanisms. The results showed that RPP treatment alleviated the symptoms of colitis in mice, including weight loss, colon shortening, and injury, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 61 publications
1
15
0
Order By: Relevance
“…In this study, as shown in Figure 5 , SGGY significantly promoted the nuclear translations of Nrf2 in SH-SY5Y cells, indicating that the protective effects of SGGY on SH-SY5Y cells were related to the activation of Nrf2. This result was consistent with the previous report that peptides could activate the Nrf2-Keap1 signaling pathway [ 39 ]. A recent study also found that a strong interaction existed between walnut-derived peptides and Keap1 by the method of molecular docking [ 26 ].…”
Section: Discussionsupporting
confidence: 94%
“…In this study, as shown in Figure 5 , SGGY significantly promoted the nuclear translations of Nrf2 in SH-SY5Y cells, indicating that the protective effects of SGGY on SH-SY5Y cells were related to the activation of Nrf2. This result was consistent with the previous report that peptides could activate the Nrf2-Keap1 signaling pathway [ 39 ]. A recent study also found that a strong interaction existed between walnut-derived peptides and Keap1 by the method of molecular docking [ 26 ].…”
Section: Discussionsupporting
confidence: 94%
“…In addition, the metabolites of polyphenols in the colon segment catabolized by microbiota results in increased anti-inflammatory activity [ 74 , 75 ]. A great number of studies have shown that polyphenolic compounds positively regulate antioxidant signaling pathways, such as Nrf2 [ 76 , 77 ], to intensify the intestinal mucosal barrier, which is also beneficial for the homeostasis of the gut microbiota [ 78 , 79 , 80 ]. Intriguingly, some microbial phenolic metabolites, which are generated through the interaction of undigested phenolic compounds and the microbiota found in the colon, have greater relevance and bioavailability than their precursors [ 12 ].…”
Section: Polyphenols Retard Oxidative Stress and Inflammation Via Mod...mentioning
confidence: 99%
“…In addition, intestinal disorders can lead to metabolic diseases, including cardiovascular diseases and cancer . Therefore, repairing the intestinal barrier and regulating gut microbiota are key targets for treating and preventing gastrointestinal inflammation and metabolic diseases. , The European Society for Clinical Nutrition and Metabolism suggested that adults with inflammatory bowel disease (IBD) should increase their protein intake to 1.2–1.5 g/kg body weight/day, compared to that consumed by the healthy population (0.83 g/kg body weight/day). , Furthermore, nutritional availability, especially that of proteins, is crucial during the illness treatment period . Therefore, the development of food-derived natural proteins as ingredients for nutritional supplements has wide application potential …”
Section: Introductionmentioning
confidence: 99%
“…13,14 Furthermore, nutritional availability, especially that of proteins, is crucial during the illness treatment period. 15 Therefore, the development of food-derived natural proteins as ingredients for nutritional supplements has wide application potential. 16 Eggs are the main high-quality proteins that are usually consumed in daily life, especially egg white proteins (EWP), which are currently one of the main sources of novel bioactive peptides.…”
Section: Introductionmentioning
confidence: 99%